Meningkatkan Kompetensi Guru Dalam Pelaksanaan Pembelajaran Melalui Supervisi Akademik - Ahmad Mujitahid (Journal of Classroom Action Research, 2022)
The purpose in this school action research is to find out the improvement of teacher competence in the implementation of learning through Academic Supervision at SD Negeri 46 Ampenan Kota Mataram Odd Semester 2018/2019. The timing of this research, namely in the odd semester of the 2018/2019 School Year, which took place from September to November 2018. The implementation process takes four stages, namely planning, implementation, observation, and reflection. The results of the study showed that: (1) The implementation of learning through academic supervision by the principal proved successful in improving the ability of state elementary school teachers 46 Ampenan in managing the learning process. Obtained the average value of improving teacher competence is Either Once 5 people or 63.00% previously in cycle I zero, and teachers who obtained either 3 people or 38% have been completed; (2) With the increasing ability of state elementary school teachers 46 Ampenan in managing the learning process, in addition to the learning process students are more meaningful and the learning results also increase; (3) Based on the analysis of the data above, the teacher in making a learning plan, and can organize learning in the school towards the desired change reaches 85% of his ability, then the increase in teacher competence is said to increase and be effective. Thus, the hypothesis of action proposed above is acceptable